A Multimodal Critical Discourse Analysis of the Representation of the Feminine Gender in Nigerian Hip-Hop Music - Olayemi, Oluwakemi Titilola (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
Hip-hop music has become a popular trend in Nigeria, with it enjoying a high level of acceptance among the Nigerian youths. It is characterised by the construction of different themes woven around vibrant styles and rhythmic patterns. This paper examines the linguistic and non-linguistic choices in hip-hop music and the messages that these choices convey about the feminine gender.  Excerpts from the lyrics of randomly selected hip-hop music serve as data. These are analysed in line with the multimodal critical discourse analysis approach which combines both Fairclough’s Critical Discourse Analysis Approach – an exploration of the relationship between texts and wider socio-cultural processes - with the investigation of meaning arising from the integrated use of semiotic resources and visual images within the text as expressed by O’ Halloran and Kress. These are based on Halliday’s systemic functional theory.  It is evident that females play major roles as characters in hip-hop music videos. The use of vulgar expressions in the description of these female characters portrays them mainly as sex commodities and this questions the dignity of the African woman and the virtues she is expected to project to her fellow female folk, home and abroad. Keywords: Critical Discourse Analysis, Feminine Gender, Hip-hop Music, Socio-Cultural  Processes, The African Woman